2015
DOI: 10.3390/molecules200611119
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities and Antibacterial Mechanism of Polygonum cuspidatum Extracts against Nosocomial Drug-Resistant Pathogens

Abstract: Abstract:Recently, drug resistance due to the extensive abuse and over-use of antibiotics has become an increasingly serious problem, making the development of alternative antibiotics a very urgent issue. In this study, the Chinese herbal medicine, Polygonum cuspidatum, was extracted with 95% ethanol and the crude extracts were further purified by partition based on solvent polarity. The antimicrobial activities of the extracts and fractions were determined by the disk diffusion and minimum inhibitory concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 21 publications
2
63
0
Order By: Relevance
“…A study conducted by Su, et al (2015) revealed that ethyl ether extraction from Polygonum cuspidatum tends to provide a promising and capable agent for therapeutic applications against nosocomial pathogens. The drug resistant gene transfer occurs due to the spread of drug resistant bacteria among different hosts.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Su, et al (2015) revealed that ethyl ether extraction from Polygonum cuspidatum tends to provide a promising and capable agent for therapeutic applications against nosocomial pathogens. The drug resistant gene transfer occurs due to the spread of drug resistant bacteria among different hosts.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activity was conducted using the disc diffusion method as adopted from Thitilertdecha et al 11 and Su et al 12 To determine the minimum inhibition concentration (MIC) of each plant extract, selected Gram positive and Gram-negative micro-organisms where treated with 4 concentrations of plant extracts from serial dilution namely: 1 mg/ml, 0.5 mg/ml, 0.25 mg/ml and 0.125 mg/ml. After serial dilutions were prepared, 6 mm filter paper discs were impregnated with the extract at each concentration.…”
Section: In Vitro Antibacterial Assaymentioning
confidence: 99%
“…Plant extracts and their derived products are recognized as alternative candidates for the treatment of infections caused by pathogenic microbes. The extracts obtained from Holarrhena antidysenterica, Larrea tridentata , Polygonum cuspidatum, as well as plant‐derived compounds such as norwogonin from Scutellaria baicalensis , and terchebulin from Terminalia chebula have been previously reported to exhibit antibacterial activity against A. baumannii. Therefore, targeting plant products could be a suitable alternate to control infections caused by A. baumannii.…”
Section: Introductionmentioning
confidence: 99%